2016
DOI: 10.1158/1541-7786.mcr-16-0034
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of the Deiminase PADI2 Is an Early Event in Colorectal Carcinogenesis and Indicates Poor Prognosis

Abstract: Peptidyl arginine deiminases (PADI) are a family of enzymes that catalyze the poorly understood posttranslational modification converting arginine residues into citrullines. In this study, the role of PADIs in the pathogenesis of colorectal cancer was investigated. Specifically, RNA expression was analyzed and its association with survival in a cohort of 98 colorectal cancer patient specimens with matched adjacent mucosa and 50 controls from donors without cancer. Key results were validated in an independent c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(56 citation statements)
references
References 52 publications
3
51
0
1
Order By: Relevance
“…The present study offers evidence that PADI2 might have deleterious effects on tumor growth and metastasis in liver cancers by upregulating EPO expression. Cantarino et al11 demonstrated that the downregulation of PADI2 is an early event in colorectal carcinogenesis, a finding that corresponds to our observation in Bel-7402 cells with suppressed PADI2 expression.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The present study offers evidence that PADI2 might have deleterious effects on tumor growth and metastasis in liver cancers by upregulating EPO expression. Cantarino et al11 demonstrated that the downregulation of PADI2 is an early event in colorectal carcinogenesis, a finding that corresponds to our observation in Bel-7402 cells with suppressed PADI2 expression.…”
Section: Discussionsupporting
confidence: 92%
“…These findings suggest that PADI2 is involved in the tumorigenesis of many tumors and plays an important role in progression. Alternatively, Cantarino et al11 demonstrated that downregulation of PADI2 is an early event in colorectal carcinogenesis. Therefore, the expression of PADI2 in various tumor types and blood of patients requires a thorough investigation.…”
Section: Introductionmentioning
confidence: 99%
“…In cancer cells, PAD2, which is the most widely expressed isozyme in the body [35], has been shown to deiminate histone H3 and play a role in gene regulation [43,70,83,84]. Recent studies are increasingly identifying multifactoral roles for PAD2 and PAD4 in cancer pathologies, depending on tumour type [71,85,86,87,88]. In gastric cancer, the PADI2 gene was found to advance abnormal cell behaviour by increasing expression levels of CXCR2, a cell proliferation and invasion gene; while PADI2 has deleterious effects on tumour growth and metastasis in liver tumour cells via regulation of the tumour growth gene erythropoietin (EPO) [71].…”
Section: Peptidylarginine Deiminases Pads In Cancermentioning
confidence: 99%
“…In gastric cancer, the PADI2 gene was found to advance abnormal cell behaviour by increasing expression levels of CXCR2, a cell proliferation and invasion gene; while PADI2 has deleterious effects on tumour growth and metastasis in liver tumour cells via regulation of the tumour growth gene erythropoietin (EPO) [71]. Colon cancer has, on the other hand, been associated with downregulation of PADI2 [86,87], while PADI2 affects differentiation of normal colon and can suppress proliferation of colonic epithelial cells through protein deimination [86,87], accompanied by arrest of cell cycle progression in G1 phase [86]. In colon cancer cells (HCT116), PAD-inhibitor Cl-amidine induces the upregulation of several tumor suppressor microRNAs, which are otherwise downregulated in cancers [89].…”
Section: Peptidylarginine Deiminases Pads In Cancermentioning
confidence: 99%
“…Previously, PADI2 function has been reported in other biological contexts, such as H3 citrullination during breast cancer oncogenesis 1618 the estrus cycle in the uterus or in gonadotrope cells 11,19,20 peptidyl citrullination during colon cancer oncogenesis 21,22 and inflammation inducing multiple sclerosis and skin neoplasia 2325 . Regarding embryonic development, other isoforms of PADI have been suggested to be involved: PADI4 was found to regulate pluripotency via H1 citrullination 26 and PADI6 was found to function during zygotic genome activation and be related to female infertility 27 .…”
Section: Discussionmentioning
confidence: 99%